2018
DOI: 10.1371/journal.pone.0207204
|View full text |Cite
|
Sign up to set email alerts
|

Association of specific gene mutations derived from machine learning with survival in lung adenocarcinoma

Abstract: Lung cancer is the second most common cancer in the United States and the leading cause of mortality in cancer patients. Biomarkers predicting survival of patients with lung cancer have a profound effect on patient prognosis and treatment. However, predictive biomarkers for survival and their relevance for lung cancer are not been well known yet. The objective of this study was to perform machine learning with data from The Cancer Genome Atlas of patients with lung adenocarcinoma (LUAD) to find survival-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…For selection of such marker features, several approaches have been proposed, e.g. Pearson chi-squared test [ 62 ], correlation test [ 27 , 62 ], variance thresholding, genetic algorithms [ 63 ], univariate feature selection, recursive feature elimination, principal component analysis [ 27 ], CUR matrix [ 64 ], decomposition [ 65 ] and covariate regression [ 66 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…For selection of such marker features, several approaches have been proposed, e.g. Pearson chi-squared test [ 62 ], correlation test [ 27 , 62 ], variance thresholding, genetic algorithms [ 63 ], univariate feature selection, recursive feature elimination, principal component analysis [ 27 ], CUR matrix [ 64 ], decomposition [ 65 ] and covariate regression [ 66 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The high-throughput sequencing technology has made it possible a comprehensive interrogation of whole transcriptome and genome of tumor tissues at an increasingly reasonable cost [4,5]. Previous studies focused on finding prognostic signatures based on gene expressio n [6][7][8][9] or mutation [10][11][12] for LUAD patients. For example, Li et al [7] reported gene expression-based models with an average C-index of 0.604 on testing datasets from TCGA-LUAD in predicting overall survival (OS).…”
Section: Introductionmentioning
confidence: 99%
“…Somatic alterations can be classified into two types: somatic point mutations (SPM), which include single nucleotide variants and indels which only affect one or a few genetic code letters, and somatic copy number variations (CNV), which involve larger contiguous portions of the genome either being lost (deletions) or duplicated (amplifications) [ 7 ]. A few studies have identified mutation features for specific cancer types, such as lung adenocarcinoma [ 8 ], acute myeloid leukemia [ 9 ], breast cancer [ 10 ] and colorectal cancer [ 11 ]. Most of these studies are conducted on a single cancer type with a single type of somatic alterations data.…”
Section: Introductionmentioning
confidence: 99%